Gambaran Kehidupan Wanita yang di Poligami - Mohammad Khasan; Sujoko Sujoko (Universitas Muhammadiyah Jember, 2020)
The phenomenon of polygamy in Indonesia is still a polemic in society. One of them was during the speech by the chairman of Indonesian Solidarity Party (PSI) Grace Natalie at East Java Expo on Tuesday (11/12/2018) which stated that